How exploitation impedes and impels exploration: Theory and evidence - Piao, Ming; Zajac, Edward J. (Strategic Management Journal, 2016)
Research summary : This study suggests that strategy and organizational scholars seeking to analyze the impact of exploitation on exploration would benefit by moving away from the generally assumed unitary perspective on exploitation. Specifically, we propose a multifaceted perspective on exploitation by theoretically and empirically distinguishing between repetitive exploitation versus incremental exploitation. We argue that repetitive exploitation can impede exploration and delay firms' responses to environmental changes, while incremental exploitation can impel exploration and accelerate firms' responses to environmental changes. We test our arguments using extensive longitudinal data from the hard disk drive ( HDD ) industry, and our supportive empirical findings highlight the relevance of our distinction between the two types of exploitation and their very different effects on exploration . Managerial summary : This study offers a solution to the puzzle of why many believe firms cannot excel at advancing existing practices and developing new initiatives, typically described as the trade‐off between exploitation and exploration. We introduce the distinction between repetitive and incremental exploitation and show that only the former type of innovation generates rigidity toward exploration, whereas the latter actually promotes exploration. More specifically, our evidence from the hard disk drive industry shows that those firms emphasizing incremental innovation (as opposed to repetition of their existing practices) were most likely to remain explorative over time, whereas firms emphasizing more repetitive innovation proved less open to changes. We discuss the implications of our findings as suggesting that firms seeking to optimize their innovativeness over the long term should strive to remain active in incrementally innovating their existing practices . Copyright © 2015 John Wiley & Sons, Ltd.